1999
DOI: 10.1046/j.1440-1819.1999.00586.x
|View full text |Cite
|
Sign up to set email alerts
|

The signal detection ability of patients with auditory hallucination: Analysis using the continuous performance test

Abstract: Signal detection theory is appropriate for analyzing the problem of whether auditory hallucination arises from a sensory or judgmental disorder. In the present study the sensory discrimination ability and decision bias of psychiatric patients with auditory hallucination was investigated by using the visual continuous performance test. Based on signal detection theory the dЈ (d prime) and the lnb value (the natural logarithm of the b value) were calculated. The dЈ is indicator of discriminating ability, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…There was some indication that this improvement in novelty detection with nicotine may be greater in those with schizophrenia than in normal control participants. Improvements in novelty detection may be of clinical significance, as irregularities in novel item recognition have been associated with positive symptoms in schizophrenia (Brebion et al 1998;Ishigaki and Tanno 1999). As in our study, prior studies have not found effects of nicotine on overall verbal memory performance in schizophrenia (Harris et al 2004;Smith et al 2006).…”
Section: Discussionsupporting
confidence: 66%
“…There was some indication that this improvement in novelty detection with nicotine may be greater in those with schizophrenia than in normal control participants. Improvements in novelty detection may be of clinical significance, as irregularities in novel item recognition have been associated with positive symptoms in schizophrenia (Brebion et al 1998;Ishigaki and Tanno 1999). As in our study, prior studies have not found effects of nicotine on overall verbal memory performance in schizophrenia (Harris et al 2004;Smith et al 2006).…”
Section: Discussionsupporting
confidence: 66%
“…Source monitoring deficits have also been observed in healthy individuals with high level of psychotic-like experiences (Laroi, DʼArgembeau, Bredart, & van der Linden, 2007;Allen, Freeman, Johns, & McGuire, 2006). Accordingly, signal detection parameter have unequivocally shown a decreased rather than increased perceptual sensitivity in patients with auditory hallucinations (Ishigaki & Tanno, 1999). Furthermore, a lowered sensitivity in detecting a mismatch between expectancy and experience was described.…”
Section: Introductionmentioning
confidence: 95%
“…One study suggests that typical antipsychotics do not have a large effect on a′ and d′ although the sample size was small (Epstein et al 1996). However, since disturbances in response bias have been correlated with hallucinations (Liu et al 1997;Ishigaki and Tanno 1999;Brébion et al 2010), it might be predicted that clozapine would exert some beneficial effects. At the very least, these data emphasise the translational potential of combining chronic intermittent PCP with the 5-CSRTT, to model cognitive deficits in schizophrenia.…”
Section: Signal Detection Analysismentioning
confidence: 99%
“…The situation with lnβ is less clear (Seidman et al 1998;Egan et al 2000;Mass et al 2000); although in general, patients show lower values of lnβ that again are exacerbated under conditions of increased attentional load (Liu et al 1997;Mass et al 2000). Reductions in a′ have been tentatively linked to thought disorder (Ito et al 1997), while disturbances in response bias, in the CPT and in other tasks, have been associated with hallucinations (Liu et al 1997;Ishigaki and Tanno 1999;Brébion et al 2010).…”
Section: Introductionmentioning
confidence: 99%